Collagen alteration in an animal model of colonic diverticulosis. Issue 5 (May 1996) - Wess, L; Eastwood, M A; Edwards, C A; Busuttil, A; Miller, A
Abstract : BACKGROUND–Changes in the structure and integrity of the colon dependent on collagen content and crosslinkage occur with age. AIMS–This study using an animal model examines colonic collagen content and crosslinkage over the lifetime of rats on fibre deficient and higher fibre diets. METHODS–Two groups of 20 rats were fed either a fibre deficient diet (1.7 g NSP (non-starch polysaccharide)/100 g) or a higher fibre diet (13.3 g NSP/100 g) for 18 months. Diverticula were identified by postmortem examination. Caecal and colonic contents were weighed and assayed for short chain fatty acids. Collagen solubility in weak acid was measured to give an indication of the nature and amount of crosslinks in the collagen of the bowel wall. RESULTS–The incidence of colonic diverticula was greater (42.1% fibre deficient rats; 0% higher fibre rats). Colonic collagen solubility index in fibre deficient rats was significantly lower than higher fibre diet fed rats (p < 0.001 in all four sections of the large bowel). Rats with diverticula had the lowest solubility index (p < 0.001 in all four sections of the large bowel). Higher fibre diet rats had increased caecal and colonic contents, caecal and colonic tissue wet weights, and greater caecal short chain fatty acids. Fibre deficient diet fed rats had more pathological abnormalities. CONCLUSIONS–This animal model permits a study of the relation between collagen crosslinkage and the development of colonic diverticulosis. A higher fibre diet protects against collagen crosslinking and this is related to a decreased incidence of diverticula.